The Silk Road : ten thousand miles through Central Asia - Hedin, Sven (Tauris Parke Paperbacks, 2009)
Linking East and West, Asia with Europe, the Silk Road was once the important trading route in the world. This title presents an account of Sven Hedin's 10,000-mile journey along the ancient Silk Road, as he carried out a mission for the Chinese to create a road linking China with the rogue province of Xinjiang